Novel insights on the steam foam process. (2nd February 2022) - Chen, Zan; Fehr, Adam; Dong, Mingzhe; Husein, Maen; Bryant, Steven
Graphical abstract: Highlights: Steam foam floods are conducted with different permeabilities and steam qualities. Foam propagation and mobility reduction factor profiles are reported. Effect of gravitational liquid drainage on steam foam behavior is investigated. Parallel sandpack tests are conducted to study conformance control performance. Detailed multi-cycle diversion of flow in parallel sandpacks is reported. Abstract: Steam foam is an effective conformance control agent for improving the sweeping efficiency during steam flooding. However, the behavior of steam foam remains not fully understood. In this study, a comprehensive experimental investigation was conducted to understand steam foam propagation and conformance control potential. In particular, the effect of liquid drainage on steam foam performance was studied for the first time. Single sandpack results show that strong foam can be generated in high permeability packs, as suggested by a stable mobility reduction factor (MRF) of ∼60. In low permeability sandpacks, MRF behind the foam front quickly declines to 2. The effect of liquid drainage is more significant when weak steam foam is present in the porous media. Successful profile control is achieved with steam foam in parallel sandpacks with a permeability contrast of 15–1. A detailed multi-cycle diversion of flow in both sandpacks is reported.